1991
DOI: 10.1203/00006450-199102000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Lipoproteins in Children Treated with Continuous Peritoneal Dialysis

Abstract: ABSTRACT. Total lipids, lipoprotein-lipids, and apolipo-VLDL-C, cholesterol in the VLDL fraction proteins were studied in plasma of 20 patients, aged 13.9VLDL-TG, triglycerides in the VLDL fraction f 3.4 y (mean f SD, range 7.4 to 19 y), who were treated with continuous peritoneal dialysis for a period of 2.1 2 1.2 (range 0.5 to 4.9) y. Measurements included total plasma cholesterol and triglycerides, triglycerides in the very low density fraction, and cholesterol in the very low density, low density, and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
4
8
0
Order By: Relevance
“…Elevated TG and total cholesterol levels have been reported in 63%-100% and 30%-100% of pediatric PD patients, respectively [27,28,29]. The present study confirms the high prevalence of hypertriglyceridemia and hypercholesterolemia in these patients.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Elevated TG and total cholesterol levels have been reported in 63%-100% and 30%-100% of pediatric PD patients, respectively [27,28,29]. The present study confirms the high prevalence of hypertriglyceridemia and hypercholesterolemia in these patients.…”
Section: Discussionsupporting
confidence: 94%
“…Although some studies revealed decreased HDL cholesterol levels [30,31], in this study there was no significant difference between the treatment group and the healthy controls. In previous studies of pediatric PD patients, apo A-I levels were found to be similar [28,30] or reduced [31], while apo B levels were elevated [28,30] compared with control subjects. Highly elevated levels of apo B were noted in our analysis, while apo A-I was normal.…”
Section: Discussionmentioning
confidence: 88%
“…The elevated plasma triglycerides, total cholesterol, LDL-cholesterol, and Apo B concentrations in patients in the present study before EPO are compatible with previous reports of type IV hyperlipidemia in patients with ESRD [34]. Pollock et al [35] studied 112 patients on hemodialysis before and after 6 and 12 months of EPO and found significant decreases in plasma triglycerides, cholesterol, and Apo B following correction of anemia.…”
Section: Discussionsupporting
confidence: 93%
“…Hypertriglyceridemia and hyperlipoproteinemia are common in patients with uremia on peritoneal dialysis [33,34]. The elevated plasma triglycerides, total cholesterol, LDL-cholesterol, and Apo B concentrations in patients in the present study before EPO are compatible with previous reports of type IV hyperlipidemia in patients with ESRD [34].…”
Section: Discussionsupporting
confidence: 93%
“…In a population of young PD patients, Scolnik and Balfe have shown that average serum cholesterol and triglyceride levels were 27% and 122% higher than the age-related normal levels [111]. Also, peritoneal losses of the low molecular weight lipoproteins results in lower levels of the protective high-density lipoproteins (HDLs) [75, 112]. In a similar study of adults the triglyceride, but not cholesterol, levels at initiation of dialysis were strong predictors of survival [113].…”
Section: Treatment Factors That May Influence Outcomementioning
confidence: 99%